HUBUNGAN MEDIA/IKLAN TERHADAP PERILAKU MEROKOK ELEKTRIK PADA SISWA SMA SWASTA DI KOTA JAMBI TAHUN 2025 - Meyviana Sekar Efrianti (Jurnal Penelitian Kesmasy, 2026)
E-cigarette smokingi (vaping) behavior is increasingi among adolescents and has become a public health issue that requires attention. This study aims to examine the relationship between media and advertising exposure and e-cigarette smoking behavior among private high school students in Jambii City in 2025. It employs a quantitative, cross-sectional research design with 191 respondents selected through random sampling. Data was collected using a questionnaire and analyzed using the Chi-Square test. The results showed that 36.6% of students were influenced by media/advertising related to e-cigarettes. Bivariate analysis showed a significant relationship between media/advertising and e-cigarette smoking behavior (p-value = 0.000), with an OR value = 3.785 (95% CI: 1.944–7.369), which means that students exposed to media/advertising have almost four times greater risk of e-cigarette smoking than students who are not exposed. In conclusion, media and advertising play an important role in shaping e-cigarette smoking behavior among adolescents, so control efforts need to focus on regulating digital advertising and strengthening media literacy in students.